Vystuplenie Dzhokhara Dudaeva . Vystuplenie Dzhokhara Dudaeva . Dzhohar Dudaev's Speech . Выступление Джохара Дудаева - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Divided opinions in government and society on the issue of Chechen sovereignty. Featured in the program: Dudayev, Dzokhar Musaevich (First President of the Self-proclaimed Republic of Ichkeriia) Раскол во властных структурах и в обществе по вопросу суверенитета Чечни. В программе участвуют: Дудаев, Джохар Мусаевич (Первый президент самопровозглашённой Чеченской Республики Ичкерия)